2020
DOI: 10.1002/bjs5.50344
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative MRI for predicting pathological changes associated with surgical difficulty during laparoscopic cholecystectomy for acute cholecystitis

Abstract: Background: Severe inflammation with necrosis and fibrosis of the gallbladder in acute cholecystitis increases operative difficulty during laparoscopic cholecystectomy. This study aimed to assess the use of preoperative MRI in predicting pathological changes of the gallbladder associated with surgical difficulty. Methods: Patients who underwent both preoperative MRI and early cholecystectomy for acute cholecystitis between 2012 and 2018 were identified retrospectively. On the basis of the layered pattern of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…As we hypothesized, LSI broadening in the gallbladder wall on preoperative MRI was significantly associated with a higher bailout procedure rate and longer operating time in early LC for AC. These results can be explained by the results of our previous study, which showed that the rate of inflammatory pathological changes such as necrosis, abscess formation, and fibrosis of the gallbladder wall significantly increased as LSI in the gallbladder wall broadened (27.4%, 84.8%, and 97.1% in the HSI, ISI, and LSI groups, respectively) [12]. There was a significant difference in operative outcomes between the HSI and LSI groups (bailout procedure rate: 6.8% vs. 40.2%; open conversion rate: 0% vs. 26.5%; operating time: 95 min vs. 138 min).…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…As we hypothesized, LSI broadening in the gallbladder wall on preoperative MRI was significantly associated with a higher bailout procedure rate and longer operating time in early LC for AC. These results can be explained by the results of our previous study, which showed that the rate of inflammatory pathological changes such as necrosis, abscess formation, and fibrosis of the gallbladder wall significantly increased as LSI in the gallbladder wall broadened (27.4%, 84.8%, and 97.1% in the HSI, ISI, and LSI groups, respectively) [12]. There was a significant difference in operative outcomes between the HSI and LSI groups (bailout procedure rate: 6.8% vs. 40.2%; open conversion rate: 0% vs. 26.5%; operating time: 95 min vs. 138 min).…”
Section: Discussionmentioning
confidence: 61%
“…Although MRI is more expensive than other examinations, such as abdominal ultrasonography [37], it provides much information at once. Our MRI assessment method is available using the HASTE sequence captured during routine MRCP, as some studies have already reported [11,12,38,39], and can be quickly introduced as part of daily radiological studies. In conclusion, MRCP/MRI could be a useful option for the comprehensive surgical management of acute cholecystitis and decision making in emergencies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations